Safety of Intra-articular Methotrexate Injection With and Without Electroporation for Inflammatory Small Joints in Patients With Rheumatoid Arthritis. Issue 12 (November 2019) - Tada, Masahiro; Inui, Kentaro; Okano, Tadashi; Mamoto, Kenji; Koike, Tatsuya; Nakamura, Hiroaki
The general disease activity of patients with rheumatoid arthritis (RA) is well controlled by disease-modifying antirheumatic drugs, but local inflammation often remains in a few small joints. Electroporation, making small pores in cell membranes, has proven useful for drug delivery. The safety of a combination therapy of methotrexate (MTX) and electroporation for local joint inflammation in RA was investigated in a prospective, randomized, double-blind, placebo-controlled, exploratory study (UMIN000016606). The patients were randomly allocated to groups receiving a combination of MTX and electroporation (True-EP) and MTX alone (False-EP) groups. The MTX solution was injected into finger joints under ultrasound guidance. The True-EP group underwent electroporation with MTX, and the False-EP group was given MTX but only pinched using the electrode. The ultrasound grade, disease activity, and safety were evaluated from baseline to 26 weeks. Five patients (3 True-EP and 2 False-EP) with a mean age of 57.4 years and disease duration of 10.2 years were enrolled. The grey-scale grade was unchanged in 3 cases (2 True-EP and 1 False-EP) and increased in 2 cases (1 True-EP and 1 False-EP). Disease activity was alleviated in 3 cases (2 True-EP and 1 False-EP). No patients experienced burned skin or electroshock. The combination therapy of electroporation and MTX was safe for RA patients.